The Role of Glucose, Serum, and Three-Dimensional Cell Culture on the Metabolism of Bone Marrow-Derived Mesenchymal Stem Cells - Byron Deorosan; Eric A. Nauman (Stem Cells International)
Mesenchymal stem cells (MSCs) have become a critical addition to all facets of tissue engineering. While most in vitro research has focused on their behavior in two-dimensional culture, relatively little is known about the cells' behavior in three-dimensional culture, especially with regard to their metabolic state. To evaluate MSC metabolism during twodimensional culture, murine bone marrow-derived MSCs were cultured for one week using twelve different medium compositions, varying in both glucose and fetal bovine serum (FBS) concentrations. The results indicate that glucose concentration was the more important factor in sustaining cell growth and viability. To evaluate metabolic state during three-dimensional culture, MSCs were cultured for one week using two different medium compositions and two different concentrations of collagen gel matrix. The medium compositions only varied in glucose concentration. The results indicate that glucose and extracellular matrix were significant factors in the metabolic response of the cells. However, cells cultured in low density collagen exhibited considerable cell death, likely because of physical contraction of the collagen hydrogel which was not observed in the higher density collagen. These findings will be useful to the development of in vitro cell culture models that properly mimic in vivo physiological processes.